Agricultural land use planning an effective means of enhancing tribal farmers' income in Asom - Ray, Prasenjit; Sharma, G. K.; Bandyopadhyay, S.; Ramachandran, S.; Jena, R. K.; Singh, S. K. (Indian Farming, 2018)
Agricultural land use planning interpretation of soil resourcedatabase and assessment of soil-site suitability for agricultural crops play important roles for the selection of suitable crop for a particular area. Proper selection of crops coupled with appropriate management practices is of tremendous importance for increasing production and profitability of farming community. This becomes moresignificant while planning for fallow lands in tribal villages. Scientific land use planning along with proper implementation are the tools forenhancing farmers’ income in agrarian society.